Liberalism and the Idea of Just Society - Pallathadka, Harikumar; Sanjeev Kumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
At the beginning of the third century, liberalism was the preferred philosophy. It is not easy to define any political party, as with conservatism. Liberal ideology dates back to the end of the seventeenth century when the political turbulence of England's middle civil wars left the nation in a state of great social upheaval. Following this, the nineteenth century is explored, and significant ideas of ‘classical' and ‘New' liberalism are described. Before the First World War, the limits of British liberalism were already apparent, and its decline was virtually total throughout the interwar period. In light of the demise of Soviet communism in the late 1980s and the subsequent rise of liberal capitalist democracy, we review the rebirth of liberalism. An investigation of some of the current failings of liberalism is conducted, and the authors predict the fate of liberalism.